The metaphysical foundations of love: Aquinas on participation, unity, and union - Flood, Anthony T. (Thomistic ressourcement series, 2018)
Love as a unitive force -- Degrees of union -- Participation and the love of God -- Conformity and sin -- The fulfillment of love in God -- The love of self and subjectivity